Development of religious tourism: perceptions of Christian Orthodoxy ecclesiastical communities and leaders - Liasidou, Sotiroula; Pericleous, Katerina; Garanti, Zanete (My University, 2025)
Purpose – This paper aims to investigate the perceptions of ecclesiastical communities and leaders on the development of religious tourism, focusing on its potential economic and social benefits while ensuring that tourism practices align with religious doctrines to preserve the sanctity and spirituality of sacred sites. Design/methodology/approach – This study uses a mixed-methods approach, combining surveys and interviews to gather insights from ecclesiastical communities. By analysing quantitative data with structural equation modelling and complementing it with qualitative insights, the research provides a comprehensive view of how these communities perceive religious tourism. Findings – The study findings indicate that religious tourism can bring substantial economic and social benefits, as long as it respects religious values and traditions. Ecclesiastical communities generally support tourism development, provided it enhances rather than detracts from spiritual experiences. While economic gains are acknowledged, the primary focus remains on preserving religious heritage and spirituality. Originality/value – The originality of this study lies in its focus on the perceptions of ecclesiastical communities and leaders regarding religious tourism development. This study contributes to the limited literature on the intersection of religious tourism and Christian Orthodoxy, offering a nuanced understanding of how tourism practices can align with religious doctrines to preserve the sanctity and spirituality of sacred sites.
Keywords: Religious tourism; Pilgrimage; Cyprus; Christian orthodox religion; Sacred places; Monasteries